2004
DOI: 10.1002/nur.20014
|View full text |Cite
|
Sign up to set email alerts
|

Severity of fecal incontinence in community‐living elderly in a health maintenance organization

Abstract: An anonymous survey containing questions about the severity of fecal incontinence (FI)--frequency, amount, and type--and its correlates was distributed to community-living elderly at four managed-care clinics. Completed surveys were received from 1,352 respondents whose mean (+/-standard deviation) age was 75 +/- 6 years and 60% of whom were female. Approximately 19% reported having FI one or more times within the past year. Incontinence that soiled underwear or was of loose or liquid consistency was most comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 35 publications
1
15
0
2
Order By: Relevance
“…This tendency to leak comparatively low volumes of loose or liquid stool is consistent with other reports. 5,7 Twenty-one percent of respondents with fecal incontinence also had urinary incontinence, which is lower than the nearly 50% reported in older community-living adults. 5,6 The lower rates reported by our respondents may be because of their younger age and comparatively good overall health.…”
Section: ■ Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This tendency to leak comparatively low volumes of loose or liquid stool is consistent with other reports. 5,7 Twenty-one percent of respondents with fecal incontinence also had urinary incontinence, which is lower than the nearly 50% reported in older community-living adults. 5,6 The lower rates reported by our respondents may be because of their younger age and comparatively good overall health.…”
Section: ■ Discussionmentioning
confidence: 62%
“…5,6 The most common type of stool that is leaked is loose or liquid in consistency. 5,[7][8][9] Although the amount of stool that is leaked varies, most people leak a small volume, usually described as enough to soil a pad or their underwear only. 4 Use of an absorbent product such as a panty liner, pad, or brief is a common self-care practice for managing fecal incontinence, especially by women.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Constipation often leads to fecal incontinence in the elderly population, with heavy laxative use producing liquid stool and subsequent overfl ow incontinence around partial or complete impaction [ 31 ]. Other factors independently associated with fecal incontinence include prior bowel resection, prior hemorrhoidectomy, loose/liquid stool, and constant fecal urgency [ 32 ]. Fecal incontinence is increasingly prevalent in institutionalized elders with rates reported over 50 %.…”
Section: Fecal Incontinencementioning
confidence: 98%
“…Some studies reported memory/cognition problems [24], physical disability [25], and functional incapacity [7] as potentially associated factors for faecal incontinence in older people. However, to keep the length of interviews within acceptable timeframes for participants in the current study, data related to these associated factors was not measured.…”
Section: Discussionmentioning
confidence: 99%